KEMAMPUAN MEMBUAT RINGKASAN TEKS BACAAN PADA SISWA KELAS V SEMESTER GANJIL SD NEGERI 2 TALANG TELUK BETUNG BANDAR LAMPUNG TAHUN PELAJARAN 2020/2021 - Saputra, Hendra (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
The problems raised in this study are related to the students' ability to compose a reading text summary. This study aims to determine and describe the level of the students' ability to compose a reading text summary in grade V SD Negeri 2 Talang Bandar Lampung. To achieve the research objectives mentioned above, the author uses descriptive quantitative methods, while the data collection technique uses test techniques. The population in this study amounted to 70 students and the number of samples in this study was determined as many as 25 people. The sampling technique used is the Stratiffied Proposional Random Sampling technique. Analyzing the data in this study is to use a percentage. The results showed that the ability to compile a reading text summary in the fifth grade students of SD Negeri 2 Talang Bandar Lampung was in the Enough category.